Systemic risk, governance and global financial stability - Ellis, Luci; Haldane, Andy; Moshirian, Fariborz (Journal of Banking & Finance, 2014)
The paper argues that while attempts have been made to reform four of the five key pillars of banks’ operation, (i.e. competition, resolution, supervisory, and auditing and valuation policies), less attention has been paid to the role of bank governance and systemic risk, despite a strong link between governance and risk-taking. The paper offers four solutions to strengthen bank governance. First, the regulatory capital base of banks could be increased. Second, the compensation structure of managers could be reformed. Third, effort could be focussed on creating and implementing resolution regimes which offer the credible prospect of “bailing-in” creditors in the event of stress and fourth solution is to reform the structure of company law– for example, by extending control rights beyond shareholders. Furthermore, the paper argues that given the diversity of the whole financial system, it is expected that the risks individual financial institutions face are also diverse. It cannot be assumed that the appropriate capitalisation is constant across all risks. While leverage ratios are a useful backstop measure and guard against potential gaming of risk-weights, their appropriate role is as a backstop. The diversity within the financial system also supports the fact that a single measure of systemic risk is unlikely to be universally applicable, nor is a single instrument of financial stability policy.